1939
DOI: 10.1104/pp.14.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Fruit Size and Food Supply in the Tomato

Abstract: Recently GUSTAFSON and STOLDT (2) made a study of the relation between leaf area and fruit size of the tomato. In this study it was found that by increasing the leaf area per fruit, the size of the fruit produced was also increased. In their experiments the leaf area was not adjusted until after the ovary had completed its growth and the fruits had set. It has therefore seemed desirable to attempt to influence the size of the fruit while the ovary is being formed as well as during the period of its development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1940
1940
1961
1961

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…When the fruit enters the period of ontogeny in which it may show symptoms of blossom-end rot, its development is characterized by cell enlargement. In this regard Houghtaling (1935) and Gustafson and Houghtaling (1939) found that little or no cell division occurs after anthesis in the ovary wall. Smith (1935), in a less detailed study of this aspect of development, reports that cell division continues until about 14 days after pollination.…”
Section: Discussionmentioning
confidence: 97%
“…When the fruit enters the period of ontogeny in which it may show symptoms of blossom-end rot, its development is characterized by cell enlargement. In this regard Houghtaling (1935) and Gustafson and Houghtaling (1939) found that little or no cell division occurs after anthesis in the ovary wall. Smith (1935), in a less detailed study of this aspect of development, reports that cell division continues until about 14 days after pollination.…”
Section: Discussionmentioning
confidence: 97%